Comparison of linear and circular polarization in foggy environments at UV-NIR wavelengths - Zeng, Xiangwei; Li, Yahong; Chen, Xueye; Zheng, Hongxia (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
This paper investigates the polarization persistence of linear polarization and circular polarization in foggy environments from ultraviolet (UV) to near-infrared (NIR). Using polarization tracking Monte Carlo simulation for varying particle size, wavelength, refractive index, and detection distance, it is shown that linear polarization and circular polarization exhibit different persistence performance. For wet haze of 0.6 μm mean diameter particles, right-handed circular polarization shows better persistence than parallel polarization at wavelengths of 0.36, 0.543 and 1.0 μm. But parallel polarization shows better persistence at wavelengths of 1.55, 2.1 and 2.4 μm. For wet haze of 1.0 μm mean diameter particles, right-handed circular polarization shows better persistence at wavelengths of 0.36, 0.543, 1.0 and 1.55 μm. But parallel polarization shows better persistence at wavelengths of 2.1 and 2.4 μm. For wet haze of 2.0 μm particles and radiation fog and advection fog, right-handed circular polarization shows better persistence at all simulated wavelengths. In short, right-handed circular polarization persists better than parallel polarization in most scenarios, however, with increasing wavelength and decreasing particle size, parallel polarization gradually persists better than right-handed circular polarization. Finally, anisotropy factor for various particle models is used to map the propagation law of right-handed circular polarization and parallel polarization.
Optica Applicata, Vol. 53, 2023, nr 1, s. 153-160
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; polarization; atmospheric scattering; forward scattering